A pipeline for proteome-scale identification and studies on hormone sensitive lipases in Mycobacterium tuberculosis. (December 2017) - Sherlin, Durairaj; Anishetty, Sharmila
Graphical abstract: Highlights: A new pipeline has been developed for identification of Hormone sensitive lipases. 10 proteins are identified as HSLs in Mycobacterium tuberculosis . LipT is annotated as a putative p -nitrobenzyl esterase. Identified a new motif "PGG" a possible characteristic motif of a subfamily of HSL. Abstract: Hormone sensitive lipases (HSLs) play an important role in the survival of M. tuberculosis during dormancy. They help in the utilization of fatty acids from stored lipids. The objective of the current study was to identify all HSLs from the proteome of M. tuberculosis H37Rv. We have developed a novel HSL identification pipeline, based on amino acid sequence homology, presence of conserved motifs and other sequence features deciphered from known HSL dataset. Through this pipeline, we identified 10 proteins as putative HSLs in M. tuberculosis. We have annotated a lipase LipT, as putative p -nitrobenzyl esterase and also identified a new motif "PGG" which is a possible characteristic motif of a subfamily of HSLs.